If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 + x + 56 = 180 Reorder the terms: 90 + 56 + x = 180 Combine like terms: 90 + 56 = 146 146 + x = 180 Solving 146 + x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-146' to each side of the equation. 146 + -146 + x = 180 + -146 Combine like terms: 146 + -146 = 0 0 + x = 180 + -146 x = 180 + -146 Combine like terms: 180 + -146 = 34 x = 34 Simplifying x = 34
| 8x+3-2=1+x | | -4q-4=36+4q | | -2t+1=65 | | 12x+30=5x-321 | | 3y=8+2y | | 0.0625=0.5*x | | 2b+5=71hslf | | 10+5+3+2=21 | | (s+t)(3s-4t)=0 | | 2(1+x)=2(1+3x)-4x | | 0.7(6x+3)=1.1-(x+3) | | 3x-3=1241+1 | | -2(6x+6)=-(-3x-3) | | 2+3i=3x+yi | | 7b-17=-66 | | 2p*3pq= | | 6x+12=2+6x+10 | | 3.2s-5=5-18s | | 6x-2(X+4)=4(5+x) | | 3a-16=-31 | | (5y+1)(5+y)=0 | | 5x^3+2x^2=20x+8 | | 3.2s-5=5-18 | | 3x+u=7 | | 3a-16=31 | | 5(1-x)=-5(6x-6) | | 223=6*x+7 | | 12.6=x*40 | | 9(-10+x)-5(2x+9)=4-x+11 | | 5x-50=15 | | -19y=2x+.05 | | 6x+2+2-3x=-4(6x-3)+3(-x-3) |